The anatomy of magic - Cervantes, J. C. (Jennifer C.) (Estrada family, 2025)
"Lilian Estrada seemingly has it all: an ob-gyn star on the rise, a master at balancing work with whirlwind romances and part of a family of fiercely loyal and exceptional women, all bound together by an extraordinary secret. The Estrada women each possess a unique power, and Lily shines with the rare gift to manipulate memories. Yet not even her mystical abilities can shield her from a harrowing event at the hospital, one that sends her powers--and her confidence--spiraling out of control. Seeking solace, Lily retreats to her family's ancestral home in Mexico, only to find herself face-to-face with a ghost from her past--Sam, the first love she never forgot. Nearly a decade since she last saw him, Sam is hardly the boy she once knew, and as old flames spark to life, Lily must navigate the mysteries of their shared history and the depths of her own heart if she hopes to control her unpredictable magic"--